Pengaruh Perubahan Arus Kas Operasi terhadap Likuiditas dan Profitabilitas pada Perusahaan Manufaktur yang Terdaftar di BEI - Wardiningsih, Reny (Lembaga Yasin AlSys, 2021)
This study aims to determine the effect of operating cash flow on liquidity and profitability in manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The population in this study were manufacturing companies in 2015-2019, which amounted to 155 companies. The sampling technique used was purposive sampling technique so that a sample of 28 companies was obtained. The data analysis technique used simple linear regression analysis. Based on the results of the t-test with SPSS IBM 20, it was found that operating cash flow had no effect on liquidity as proxied by the Current Ratio (CR) because the t-count value was smaller than t-table (0.427 < 1.665) and significant value (0.670 > 0.05), and operating cash flow has an effect on profitability which is proxied by Return On Assets (ROA) because the value of t-count is greater than t-table (2.646 > 1.665) and significant value (0.010 < 0,05).